PENGEMBANGAN LKPD ELEKTRONIK BERMUATAN NOS (NATURE OF SCIENCE) PADA MATERI ASAM BASA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Noni Dwi Tifani; Sura Menda Ginting; Rina Elvia (ALOTROP, 2026)
This research was a development of an electronic Student Worksheet (e-LKPD) based on the Nature of Science (NOS) on Acid-Base topics, which aimed to determine the feasibility level of the LKPD, students responses, and the improvement of students learning outcomes. The worksheet development used the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The LKPD was validated by three expert validators, a small-scale trial involved 12 students from class XII IKM 2, whilst a large-scale trial involved 35 students from class XI IKM 2 at SMAN 7 North Bengkulu. Data collection was conducted using interview sheets, needs assessment questionnaires, validation sheets, students response questionnaires, and test instruments. The feasibility test by experts yields an average percentage of 87.27%, categorised as very feasible. Participant responses to the LKPD show an average percentage of 85%, which is in a very good category. The N-Gain score for learning outcomes is 0.43, indicating a moderate category. Based on the research results, it is concluded that the NOS-embedded LKPD on acid-base chemistry is declared very feasible for learning and improving students learning outcomes.  Keywords: Student Worksheet, Nature of Science, Acid-Base, Learning Outcomes, Development